Comparison between Pipelle Sampling and Hysteroscopy Guided Biopsy in Histologic Evaluation of Endometrium in Tertiary Care Hospital in Pakistan - Sadaf Kashif, Ghazala Iftikhar, Shagufta Jabbar, Naila Khawar, Mubashira Nasir Qureshi, Saima Siddiq Choudhry (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Abnormal uterine bleeding is one of the commonest issues in perimenopausal age group. The proportion is 9-30% in reproductive age group. This extent rises to 70% in perimenopausal and postmenopausal women’s. Irregular uterine dying (AUB) warrants an intensive assessment in perimenopausal females and subsequently it’s vital to perform it in a cost-effective way with available resources. Objective: To compare the efficacy of Hysteroscopic guided biopsy and endometrial cytology To find out the efficacy of endometrial cytology in detecting different normal and abnormal endometrial patterns Study design & Settings: It is a prospective comparative study conducted at Social Security Hospital, Multan Road, Lahore included patients 30 years and above with the chief complaints of abnormal uterine bleeding. Study Duration: 01 year January 2020 to December 2020 Sample: 100 patients Inclusion Exclusion Criteria: Females having symptoms of abnormal uterine bleeding and age above than 30 years are included in the study. The females who are pregnant and having infection or malignancy are excluded from the research Results: This Planned comparative hospital-based study was done in one hundred patients with abnormal uterine bleeding taken after the informed consent, inclusion and exclusion criteria. Endometrial thickness was assessed and all cases with <5 mm thickness will be avoided from the study. Mean age of the patient was found 45 and standard deviation 7.43. Practical implication Conclusion: To get the endometrial sample by pipelle technique is a safe procedure. It has high specificity, sensitivity, positive and negative predictive values when compared to hysteroscopy. In this way, to obtain adequate endometrial sample, Pipelle biopsy should be considered as important way of investigation. Keywords: Abnormal uterine bleeding, Pipelle, Endometerial sampling, FIGO